HARP2 pre-launch calibration: dealing with polarization effects of a wide field of view - N. Sienkiewicz; J. V. Martins; J. V. Martins; B. A. McBride; B. A. McBride; X. Xu; X. Xu; A. Puthukkudy; A. Puthukkudy; R. Smith; R. Smith; R. Fernandez-Borda; et al. (Atmospheric Measurement Techniques)
The Hyper-Angular Rainbow Polarimeter (HARP2) is a wide-field-of-view (FOV) polarimeter built for the NASA Plankton Aerosol Cloud and Ocean Ecosystem (PACE) mission launched in early 2024. HARP2 measures the linear Stokes parameters across a 114° × 100° (along-track by cross-track) FOV. In the fall of 2022, HARP2 underwent calibration at NASA Goddard Space Flight Center (GSFC) Calibration Laboratory (Code 618). HARP2 was characterized for radiometric and polarimetric response across its FOV. We have used telecentric calibration methodology on prior iterations of HARP that involved the normalization of pixels across the FOV such that calibration parameters determined at the center of the charged coupled device (CCD) detector can be used across the entire scene. By using a dual-axis yaw–pitch motorized mount, we devised two scan patterns to evaluate this methodology for HARP2. The results show that pure intensity measurements do indeed vary minimally across the FOV and therefore can utilize the flat-field normalization (telecentric) technique. On the other hand, images of polarized targets change significantly across the FOV, and calibration parameters determined at the center of the detector used in the wide FOV perform significantly worse than calibration parameters determined at or near to the location of the test (up to 5 % mean absolute uncertainty in degree of linear polarization, DoLP). We evaluated the use of a paraboloid fit of the polarized calibration parameters, at discrete FOV locations, to determine those parameters at a pixel-level resolution. According to the wide-FOV results, this process shows a marked improvement for fully polarized (DoLP = 1) calibration data to less than 1 % uncertainty after using the paraboloid fit. These results are important for the development of any wide-FOV polarimeter, especially those like HARP2 which use a front lens which causes significant barrel distortion and a division of amplitude central optical element leveraging multiple reflections. Full characterization of the source of these optical effects remains a part of future work, but the improved methodology over the telecentric method is currently being implemented in the HARP2 L1B calibration pipeline pending internal review of the implementation in the HARP Image Processing Pipeline.